2023
DOI: 10.1002/cssc.202300947
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Reduction Reaction to Ammonia on Transition Metal Carbide Catalysts

Viktor Ellingsson,
Atef Iqbal,
Egill Skúlason
et al.

Abstract: The development of a low‐cost, energy‐efficient, and environmentally friendly alternative to the currently utilized Haber‐Bosch process to produce ammonia is of great importance. Ammonia is an essential chemical used in fertilizers and a promising high‐density fuel source. The nitrogen reduction reaction (NRR) has been explored intensively as a potential avenue for ammonia production using water as proton source, but to this day a catalyst capable of producing this chemical at high Faradaic efficiency (FE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…The reason for the choice of organic solvents refers to the higher solubility of dinitrogen therein compared to water, which may result in higher ammonia selectivity. Despite this, aqueous electrolytes are most promising for future scale up due to their simplicity, non-toxicity, and low cost, which is a significant advantage over organic solvents [14], and this justifies the search of efficient electrocatalyst for selective formation of ammonia in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the choice of organic solvents refers to the higher solubility of dinitrogen therein compared to water, which may result in higher ammonia selectivity. Despite this, aqueous electrolytes are most promising for future scale up due to their simplicity, non-toxicity, and low cost, which is a significant advantage over organic solvents [14], and this justifies the search of efficient electrocatalyst for selective formation of ammonia in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, because of a high overpotential as well as the competing hydrogen evolution reaction (HER), most reported catalysts for NRR exhibit poor activity and selectivity. 9 To date, a number of NRR electrocatalysts are based on transition metals (TMs), 10–12 such as oxides, 13,14 carbides, 15,16 nitrides 17,18 and sulfides, 19 as well as metal-free catalysts 20,21 have been developed and widely noted. Wang et al found that Fe 3 O 4 @rGO hybrids synthesized by in situ redox hydrothermal method have excellent activity, selectivity and stability as NRR catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Consequently, the majority of NRR endeavors report a limited ammonia yield and faradaic efficiency. So far, a variety of electrocatalysts for the NRR have been developed, including noble metals, 25,26 transition metal sulfides, 27 transition metal nitrides (TMN), 28−31 transition metal oxides (TMO), 32,33 transition metal oxynitrides (TMON), 34,35 transition metal carbides (TMC), 36 transition metal carbonitrides (TMCN), 37,38 and metal-free materials. 39−44 Enhancing NRR performance requires comprehensive optimization of the entire electrochemical system, encompassing the cell configuration, electrolyte, and electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a variety of electrocatalysts for the NRR have been developed, including noble metals, , transition metal sulfides, transition metal nitrides (TMN), transition metal oxides (TMO), , transition metal oxynitrides (TMON), , transition metal carbides (TMC), transition metal carbonitrides (TMCN), , and metal-free materials. Enhancing NRR performance requires comprehensive optimization of the entire electrochemical system, encompassing the cell configuration, electrolyte, and electrocatalysts . Notably, electrocatalysts play a crucial role in accelerating reaction rates and improving the selectivity and efficiency in electrochemical NRR systems.…”
Section: Introductionmentioning
confidence: 99%